A comparative study on the antimicrobial resistance pattern of Klebsiella pneumoniae isolated from hospital wastewater and its surrounding community - Oyishi, Ferdous Mahmod; Islam, Anika (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.